'Confident' and 'hot' or 'desperate' and 'cowardly'? Meanings of young men's sexting practices in youth sexting culture. (27th May 2020) - Setty, Emily
ABSTRACT: Young men tend to be constructed as being at low risk of harm and able to extract value from sexting, compared to young women. Drawing upon findings from a qualitative study exploring practices and perceptions of sexting among 14–18 year-old participants in southeast England, I discuss the meanings and norms surrounding young men's sexting practices. I outline how these meanings and norms underpinned perceptions regarding the value available to young men through sexting. Young men were not, however, equally able to extract value and social capital through sexting, and participants discussed examples of the social shaming of young men who sext. I discuss how young men took up diverse positions with regard to masculine heterosexuality within youth sexting culture, in which they reworked and challenged the ideals and assumptions inherent to 'hegemonic masculinity'. I draw two conclusions: firstly, it should not be assumed that young men are inherently able to gain value through sexting; secondly, narratives of risk and shame may mean that while young men distance themselves from sexting, gendered assumptions and inequalities regarding bodily and sexual expression remain.